2016
DOI: 10.1007/s10333-016-0558-7
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent drainage in paddy soil: ecosystem carbon budget and global warming potential

Abstract: Intermittent drainage of rice fields alters soil redox potential and contributes to the reduction of CH 4 emission and thus may reduce net global warming potential (GWP) during rice cultivation. Incorporation of green biomass helps maintaining soil organic matter, but may increase CH 4 emission. We investigated net ecosystem carbon budget (NECB) and net GWP under two water management regimes-continuous flooding and intermittent drainage-having four biomass incorporation levels (0, 3, 6 and 12 Mg ha -1 ). Water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…On annual basis, the GWP of submerged rice cultivation increases by 400% with cover crops compared to fallow (Haque et al, 2015). The GWP was found to increase linearly with the amount of cover crop biomass (Haque et al, 2017), and especially with high C/N ratio of non-leguminous cover crops (Kim et al, 2013).…”
Section: Cover Crops Increase Ghg Fluxmentioning
confidence: 96%
See 1 more Smart Citation
“…On annual basis, the GWP of submerged rice cultivation increases by 400% with cover crops compared to fallow (Haque et al, 2015). The GWP was found to increase linearly with the amount of cover crop biomass (Haque et al, 2017), and especially with high C/N ratio of non-leguminous cover crops (Kim et al, 2013).…”
Section: Cover Crops Increase Ghg Fluxmentioning
confidence: 96%
“…To reduce the amount of GHG emission from rice cultivation, using cover crops with low C:N ratio (i.e., legume) (Kim et al, 2013) is recommended, apart from using intermittent, instead of continuous flooding (Haque et al, 2017). In addition to fertilizer management, alternate wetting and drying methods, and midseason drainage have successfully been used to reduced CH4 emission from rice fields without negatively affecting yield (Liang et al, 2017).…”
mentioning
confidence: 99%
“…However, it is much difficult to include SOC changes in this study for two reasons. On the one hand, only four studies from two sites were found that synchronously investigated effects of non-continuous flooding practices on GHG emissions and SOC changes to allow analyzing effects on net GWP (Haque et al, 2016(Haque et al, , 2017(Haque et al, , 2021Wu et al, 2018). Therefore, it is not feasible to conduct reliable global predictions based on RF modelling approach.…”
Section: Limitationsmentioning
confidence: 99%
“…Using cover crops with low C/N ratios (i.e. legume) and practicing intermittent, instead of continuous flooding, is recommended to reduce methane emission with minimum impact on yield (Haque et al, 2017). When it comes to biochar application, one should carefully consider the appropriate rate and method (e.g.…”
Section: Recommendations Before Implementing the Practicementioning
confidence: 99%